Theoretical analysis of the reasonable support capacity based on voussoir beam structure for a given load of the loose body under an extremely close goaf - Ren, Yuqi; Li, Yang; Lei, Xinghai; Ou, Xiangji; Wang, Nan; Li, Guoshuai; Yang, Kunpeng (Frontiers in Earth Science, 2022)
With the growing popularity of fully mechanized longwall mining, the hydraulic shield has emerged as the most crucial piece of equipment whose rated support capacity is a significant assurance for the safe extraction of coal seams. Based on the extraction in the 1692 panel of No.9 coal seam in Qianjiaying coal mine, a detailed study of the reasonable shield support capacity under extremely close goaf is carried out by using field measurement, theoretical analysis, and system development. The results show that the ZY4800-13/32 shield employed in 1692 panel is unreasonable with a large surplus coefficient of support capacity and a low support utilization rate. The voussoir beam structure with a given load of the loose body is established to calculate the shield support capacity when the lower coal seam is extracted under an extremely close goaf. After calculation, the calculated shield support capacity is 3560.03 kN in the No.9 coal seam, whereas the rated support capacity should be 4000 kN. A " calculation and analysis system of shield support capacity under the given load of loose body " is developed using the GUI module of Matlab software, which is used to examine the influence degree of relevant parameters of the immediate roof, main roof, and loose body on the shield support capacity. The thickness of the main roof has the greatest influence on the shield support capacity. Finally, pre-splitting of the main roof can be applied as an effective method to control the breaking length and reduce shield support capacity through existing research.